Blockchain technology impact on supply chain management - Rebelo, Joana Filipa Campos (2019)
Constant technological innovation is the current reality for businesses and people. Most of the technologies have great potential beyond what they are designed for. Blockchain, the underlying distributed ledger technology of Bitcoin, has only recently begun to be tested for other uses. This paper studies Blockchain technology and its applications to supply chains. The concept of Blockchain technology will be scrutinized and its implementation benefits and limitations presented. Furthermore, the use cases and benefits of Blockchain technology for supply chains will be analyzed. The paper is complemented with examples and achievements of organizations testing the technology and experts opinions on the technology and its future.